Gut transcriptome of replete adult female cattle ticks, Rhipicephalus (Boophilus) microplus, feeding upon a Babesia bovis-infected bovine host - Heekin, A.M.; Guerrero, F.D.; Bendele, K.G.; Saldivar, L.; Scoles, Glen A.; Dowd, S.E.; Gondro, C.; Nene, Vishvanath M.; Djikeng, Appolinaire; Brayton, K.A. (Springer, 2013)
As it feeds upon cattle, Rhipicephalus (Boophilus) microplus is capable of transmitting a number of pathogenic organisms, including the apicomplexan hemoparasite Babesia bovis, a causative agent of bovine babesiosis. The R. microplus female gut transcriptome was studied for two cohorts: adult females feeding on a bovine host infected with B. bovis and adult females feeding on an uninfected bovine. RNA was purified and used to generate a subtracted cDNA library from B. bovis-infected female gut, and 4,077 expressed sequence tags (ESTs) were sequenced. Gene expression was also measured by a microarray designed from the publicly available R. microplus gene index: BmiGI Version 2. We compared gene expression in the tick gut from females feeding upon an uninfected bovine to gene expression in tick gut from females feeding upon a splenectomized bovine infected with B. bovis. Thirty-three ESTs represented on the microarray were expressed at a higher level in female gut samples from the ticks feeding upon a B. bovis-infected calf compared to expression levels in female gut samples from ticks feeding on an uninfected calf. Forty-three transcripts were expressed at a lower level in the ticks feeding upon B. bovis-infected female guts compared with expression in female gut samples from ticks feeding on the uninfected calf. These array data were used as initial characterization of gene expression associated with the infection of R. microplus by B. bovis.